Answer:
x = 4
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Explanation:
Step 1: Define Equation
-4(x + 2) = 4(2 - 2x)
Step 2: Solve for x
- Divide -4 on both sides: -(x + 2) = 2 - 2x
- Distribute negative: -x - 2 = 2 - 2x
- Add 2x on both sides: x - 2 = 2
- Add 2 on both sides: x = 4
Step 3: Check
Plug in x into the original equation to verify it's a solution.
- Substitute in x: -4(4 + 2) = 4(2 - 2(4))
- Multiply: -4(4 + 2) = 4(2 - 8)
- Add/Subtract: -4(6) = 4(-6)
- Multiply: -24 = -24
Here we see that -24 does equal -24.
∴ x = 4 is the solution to the equation.